A intersetorialidade no enfrentamento ao uso abusivo de substâncias psicoativas por crianças e adolescentes no município de Foz do Iguaçu - Domareski, Viviane Heineck (2022)
This dissertation discusses the intersectoral theme, relating it to public policies designed and implemented by the Municipality of Foz do Iguaçu with actions aimed at the treatment of children and adolescents in a situation of abusive use of psychoactive substances. Studies on this topic show that legislation and the various institutions that formulate public policies defend the need for intersectoral articulation as a way of overcoming problems related to mental health and, based on this understanding, the municipality of Foz do Iguaçu, in Paraná, articulates a cross-sectoral experience that is under construction. The general objective is to know the intersectoral network, in order to identify the role of the various bodies and equipment that serve children and adolescents in a situation of abusive use of PAS, and if, from the professionals' point of view, following the intersectoral protocol, according to local demands, the sufficiency of the service would be guaranteed. As a result of this general objective, there are specific objectives: to create a normative and literary review on the protection of Rights and public mental health policies aimed at the care of children and adolescents; describe the research site, consisting of a triple border and the vulnerability of children and adolescents in this space; and to present the perception of health professionals about the local network and its functionality. Access to these professionals was through qualitative, descriptive and exploratory research, through the application of semi-structured questionnaires to professionals working at different points in the intersectoral network, in the period between December 2020 and January 2021, after approval by the ethics in research with human beings. Data analysis was carried out using the content analysis framework. It was possible to observe that care for children and adolescents, users of psychoactive substances in the city of Foz do Iguaçu, is developed with characteristics of an intersectoral network, with the construction of intersectoral instruments, which can be understood as a process of collective work. The research subjects positively evaluate the way the network was established, but point out the weaknesses for its effectiveness. It is concluded that the intersectoral experience of the Municipality is under construction, requiring additional adjustments in its development, for the expansion of policies aimed at the care of children and adolescents who use psychoactive substances.